Isolation and characterization of acetylcholinestrase inhibitors from Aquilaria species for treatment of Alzhimer Disease (AD) / Hirbod Bahrani - Bahrani, Hirbod (2013)
Aquilaria subintegra locally known as “Gaharu” belongs to the Thymelaeceae family. Its leaves have been claimed by Malay traditional practitioner in Malaysia were effective for the treatment of Alzheimer’s disease (AD). However, there is no scientific evidence available to support these claims. The AD is one of the most common neurodegenerative disorders and it causes dementia with aging. The acetylcholesterase (AChE) inhibitors were used for the treatment of AD. In this research the leaves and stem chloroform extract of A. subintegra were tested for AChE inhibitory activity. The TLC results of the leaves and stem of A. subintegra showed the presence of phenols, flavonoids, terpenoids, and alkaloids compounds in the extracts. The total phenol contents in the leaves and stem chloroform extracts were 164mgGAE/g and 210mgGAE/g respectively. Whereas, the total flavonoids contents in leaves and stem chloroform extracts were 414mgQE/g and 645mgQE/g respectively. The analysis of the stem chloroform extracts with LCMS/MS displayed that it contain kaempferol 3,4,7-trimethyl ether. The AChE inhibitory activity of leaves, stem chloroform extracts and kaempferol were 80%, 93% and 85.8% respectively. Brine Shrimp Lethality Assay (BSLA) exhibited LC50=11.64μg/ml of leaves chloroform extract, LC50=3.11μg/ml of stem chloroform extract, and LC50=9.59μg/ml for kaempferol. The response of leaves, stem chloroform extracts and kaempferol were perceived in Radial Arm Maze (RAM) through oral gavage to ICR male and female mice with impaired memory by valium. Administration of kaempferol to the mice significantly reduced the number of repeated entries to arms of maze in male and females rats. In conclusion, it could be postulated that the inhibition of AChE by leaves and stem chloroform extracts of A. subintegra could be due to the presence of kaempferol. Thus, it is safe to be used as a natural AChE inhibitor instead of berberine for the treatment of AD.